Neurohypophysial and paracrine vasopressinergic signaling regulates aquaporin trafficking to hydrate marine teleost oocytes - Ferré, Alba; Chauvigné, François; Gozdowska, Magdalena; Kulczykowska, Ewa; Finn, Roderick Nigel; Cerdà, Joan (Frontiers in Endocrinology, 2023)
The dual aquaporin (Aqp1ab1/Aqp1ab2)-mediated hydration of marine teleost eggs, which occurs during oocyte meiosis resumption (maturation), is considered a key adaptation underpinning their evolutionary success in the oceans. However, the endocrine signals controlling this mechanism are almost unknown. Here, we investigated whether the nonapeptides arginine vasopressin (Avp, formerly vasotocin) and oxytocin (Oxt, formerly isotocin) are involved in marine teleost oocyte hydration using the gilthead seabream (Sparus aurata) as a model. We show that concomitant with an increased systemic production of Avp and Oxt, the nonapeptides are also produced and accumulated locally in the ovarian follicles during oocyte maturation and hydration. Functional characterization of representative Avp and Oxt receptor subtypes indicates that Avpr1aa and Oxtrb, expressed in the postvitellogenic oocyte, activate phospholipase C and protein kinase C pathways, while Avpr2aa, which is highly expressed in the oocyte and in the follicular theca and granulosa cells, activates the cAMP-protein kinase A (PKA) cascade. Using ex vivo, in vitro and mutagenesis approaches, we determined that Avpr2aa plays a major role in the PKA-mediated phosphorylation of the aquaporin subdomains driving membrane insertion of Aqp1ab2 in the theca and granulosa cells, and of Aqp1ab1 and Aqp1ab2 in the distal and proximal regions of the oocyte microvilli, respectively. The data further indicate that luteinizing hormone, which surges during oocyte maturation, induces the synthesis of Avp in the granulosa cells via progestin production and the nuclear progestin receptor.Collectively, our data suggest that both the neurohypophysial and paracrine vasopressinergic systems integrate to differentially regulate the trafficking of the Aqp1ab-type paralogs via a common Avp-Avpr2aa-PKA pathway to avoid competitive occupancy of the same plasma membrane space and maximize water influx during oocyte hydration.